Implementation of Creating Shared Value (CSV) in the Community Empowerment Program "Cardamom Spice Village" PT Industri Jamu dan Farmasi Sido Muncul Tbk - Monika Anggun; Fitriyani, Nurul Ardian; Hadi Hartojo (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
This article was conducted to find out the implementation of the partnership program on the Creating Shared Value (CSV) concept of PT Industri Jamu Dan Farmasi Sido Muncul Tbk on cardamom farmers and what activities are carried out during the community empowerment program at the Kridoyuwono Farmer Group in Sambirata Village, Cilongok District, Banyumas Regency. This program aims to empower ginger farmers as raw material suppliers, especially cardamom commodities. One of the obstacles faced by the farmer group is the post-harvest drying process. This is due to unfavorable weather with high rainfall of 3000 mm/year (Source: BPS 2017), resulting in a disrupted drying process which in turn cannot dry the cardamom perfectly and has the potential to rot, which results in lower selling prices. The method used is a survei through social mapping, planning, and evaluation monitoring. Based on the results of the village potential analysis, there is a Micro Hydro Power Plant (PLTMH) that can be utilized as an energy source for the drying machine. With this drying machine, the post-harvest process becomes more effective and the quality of cardamom can match the raw material standards set by Sido Muncul. This program is expected to improve farmers' economy and increase farmers' resources related to cardamom cultivation.